1989
DOI: 10.1007/bf03392475
|View full text |Cite
|
Sign up to set email alerts
|

Logic, Reasoning, and Verbal Behavior

Abstract: This paper analyzes the traditional concepts of logic and reasoning from the perspective of radical behaviorism and in the terms ofSkinner's treatment ofverbal behavior. The topics covered in this analysis include the proposition, premises and conclusions, logicality and rules, and deductive and inductive reasoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…"Science studies," as such, are conducted from historical (Gruber, 1974;Shapin, 1994), sociological (Bloor, Barnes, & Henry, 1996;Merton, 1973), and psychological (Feist & Gorman, 1998;Gholson, Shadish, Neimeyer, & Houts, 1989) perspectives, with the last of these largely informed by research and theory in social, developmental, and cognitive psychology (e.g., Giere, 1988;Gopnik, 1996;Khlar, 2000;Shadish & Fuller, 1994). A behavior-analytic approach to the science of science, in contrast, remains to be more fully developed (see Burton, 1980;Creel, 1987;Fraley, 1996;Johnston & Pennypacker, 1993;Lee, 1985;Marr, 1986;Schnaitter, 1980;Skinner, 1956b;Skinner, 1957c, pp. 418-431; Terrell & Johnston, 1989).…”
Section: The Science Of Sciencementioning
confidence: 99%
“…"Science studies," as such, are conducted from historical (Gruber, 1974;Shapin, 1994), sociological (Bloor, Barnes, & Henry, 1996;Merton, 1973), and psychological (Feist & Gorman, 1998;Gholson, Shadish, Neimeyer, & Houts, 1989) perspectives, with the last of these largely informed by research and theory in social, developmental, and cognitive psychology (e.g., Giere, 1988;Gopnik, 1996;Khlar, 2000;Shadish & Fuller, 1994). A behavior-analytic approach to the science of science, in contrast, remains to be more fully developed (see Burton, 1980;Creel, 1987;Fraley, 1996;Johnston & Pennypacker, 1993;Lee, 1985;Marr, 1986;Schnaitter, 1980;Skinner, 1956b;Skinner, 1957c, pp. 418-431; Terrell & Johnston, 1989).…”
Section: The Science Of Sciencementioning
confidence: 99%
“…The results of this finding revealed that reasoning skills hold a very better place in the performance of students in Civic. Similar findings such as Terrel and Johnson (1989), Cavallo (1996), Yenilmez, Sungur, and Tekkaya (2006), Yilmaz and Alp (2006), Yong (2007) as well as James (2011) gave credence to the evidence that there was positive relationship between verbal reasoning and students' academic performance.…”
Section: Discussionmentioning
confidence: 63%
“…The study population included children under the age of 12 years whose duration of exposure was measured. Ravens standard progressive matrices [ 23 ], Wechsler Preschool and Primary Scale [ 24 ], Graphic Test of Reasoning (GTR) [ 25 ], Beery-Buktenica Developmental Test of Visual-Motor Integration (VMI) defined as the coordination of fine motor and visual perceptual abilities, Saudi-Based standard scores, and TONI Saudi-based scores and rank percentile were applied in the studies for measuring the IQ [ 26 ]. The possible score of IQ measurements for determining brain intelligence function was almost the same in these different scales.…”
Section: Methodsmentioning
confidence: 99%